PELATIHAN PEMBENTUKAN KOPERASI BAGI UMKM DAN ENTREPRENEUR MUDA DI JURANG MANGU - Soeharjoto Soekapdjo (Jurnal Pengabdian Barelang, 2020)
Cordova Bina Amanah entrepreneurship school located at Jurang Mangu, Pondok Aren, South Tangerang, Banten, is managed by social institutions, which accommodates young people who want to get an education that can be used as provisions to become entrepreneurs around the Jurang Mangu . In developing their education, the school collaborates with FEB Trisakti University which conducts Community Service there using the training method. The air of this community service carried out to increasing knowledge in the field of entrepreneurs and cooperatives, in order to support the improvement of people's welfare, with the hope of obtaining an outcome in the form of increased knowledge of entrepreneurs and cooperatives. Training material provided are procedures for establishing cooperatives, the role of member participation in cooperatives, cooperative organizations, and contracts and transactions in sharia business. The post-implementation results were as expected, due to an increase in the ability of participants on average by 33.75 percent, which before the training was only 45 percent to 78.5 percent.